Aerobic Vaginitis Induced by Escherichia coli Infection During Pregnancy Can Result in Adverse Pregnancy Outcomes Through the IL-4/JAK-1/STAT-6 Pathway - Fan, Chong; Dai, Youjin; Zhang, Lei; Rui, Can; Wang, Xinyan; Luan, Ting; Fan, Yuru; Dong, Zhiyong; Hou, Wenwen; Li, Ping; Liao, Qinping; Zeng, Xin (Frontiers in Microbiology, 2021)
Aerobic vaginitis (AV) occurred when normal vaginal microflora is dominated by aerobic bacteria, seriously affects not only female health, but also fetal health while they are pregnant. Besides, pregnant status also aggravates the symptoms and consequences of the infection. Here, we infected pregnant female BALB/c mice with Escherichia coli (E. coli) at embryonic day 4.5 (E4.5)　as study group, and equivalent PBS were inoculated as control group for subsequent research. Recorded weight of pregnant mice, as well as fetal mice, in E. coli group decreased in comparison with control group. Nevertheless, the weight of placenta increased in E. coli group. Then, five significantly upregulated genes and fifteen downregulated genes were screened by and preliminary validation demonstrated that interleukin 4 (IL4) mRNA expression in the E. coli group reduced to 18.5% and enzyme-linked immunosorbent assay (ELISA) results manifested that the level of IL4 in the plasma declined in E. coli group at E11.5 and E18.5. Next, chemokine (c-c motif) ligand 17 (CCL17), CCL22, CCL24, IL4, Janus Kinase-1 (JAK1), signal transducer and activator of transcription 6 (STAT6), and GATA3 mRNA expression all showed significant downregulation in placental and uterine tissues. Subsequent flow cytometry of primary decidual macrophages revealed more M1-like macrophages were found in E. coli group. And after added with IL4 into primary macrophages, more M1 polarized to M2 type macrophages. Moreover, we did not discover the bacteria existed in the placenta. Our study affords a feasible method for exploring and managing AV, as well as other infections, during pregnancy.